Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For some reason I cannot figure out how the book is finding the solution to this problem.

find the inverse function of $f(x)=3x\sqrt{x}$.

My steps seem to lead to a dead end:

step 1. switch $f(x)$ with $y$: $y = 3x\sqrt{x}$

step 2. swap $x$ and $y$: $x = 3y\sqrt{y}$

step 3. solve for $y$:

step 3.1: $\displaystyle \frac{x}{3y} = \sqrt{y}$.

step 3.2: $\displaystyle \left(\frac{x}{3y}\right)^2 = \left(\sqrt{y}\right)^2$

step 3.3: $\displaystyle \frac{x^2}{9y^2} = y$ ... uhhh?

The book answer is $\displaystyle y = \left(\frac{x}{3}\right)^{2/3}$.

share|improve this question
    
As always, thanks Arturo Magidin for cleaning up the post, and converting the mathematics into LaTeX. –  Eric Naslund Feb 14 '11 at 0:54
3  
+1 for showing your work. –  Arturo Magidin Feb 14 '11 at 0:54

5 Answers 5

up vote 3 down vote accepted

Nothing wrong with what you've done so far, you just haven't finished!

From $\displaystyle \frac{x^2}{9y^2} = y$, move all the $y$'s to the same side:

step 3.4: $x^2 = 9y^3$.

Now isolate $y$:

step 3.5: $\displaystyle\frac{x^2}{9} = y^3$.

Now solve for $y$ by taking cubic roots; you might also notice that the left hand side is a perfect square...

share|improve this answer

Note that $\frac{x^2}{9}=\left(\frac{x}{3}\right)^2$. Also note that you can multiply both sides of your equation by $y^2$ to get just one $y$ term, and that the cube root is the same as the $\frac{1}{3}$ power.

You could, as lhf indicates, avoid ever breaking up the $y$ terms in the first place. Technically this would be preferred, because when you divided by $y$ you made the assumption that $y\neq 0$, which is not always true.

Beware of squaring when solving equations in general, because it can lead to extraneous solutions. In this case it is a valid step, but for a silly example consider trying to solve the equation $\sqrt{y}=-1$ by squaring both sides.

A final remark. The original function has an implicit domain, $x\geq 0$. Your inverse function has a formula definition that does not appear to require any domain restriction, but it is misleading to say that $f^{-1}(x)=\left(\frac{x}{3}\right)^{2/3}$ without mentioning that this is only valid when $x\geq 0$. This domain restriction arises from the fact that the range of $f$ is $[0,\infty)$. The function $h(x)=\left(\frac{x}{3}\right)^{2/3}$ on the whole real line is not invertible (it fails the horizontal line test), whereas if $g(x)=-f(x)=-3x\sqrt{x}$, then the inverse function would be $g^{-1}(x)=\left(\frac{x}{3}\right)^{2/3}$ on $(-\infty,0]$. Looking at the graphs of these functions and keeping in mind how inverses are reflected across the line $y=x$ (resulting from switching $x$ and $y$) should make it clearer what is going on.

share|improve this answer

$x=3y\sqrt y$ implies $x^2=9y^3$.

share|improve this answer

The algorithm you are applying is correct, and will yield the inverse function. In step 3 you should square both sides. Then we get $$x^2=9y^2\cdot y=9y^3$$

Can you solve the problem from here?

Hint: Divide by $9$ and then take cube roots.

Hope that helps.

share|improve this answer

Two hints: $\sqrt{x}=x^{\underline{?}}$ and $x^a\cdot x^b=x^{\underline{?}}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.